Effect of Classroom Learning Environment on Basic Science Students' Academic Achievement and Retention at Upper Basic Education Level - Obodo, Abigail Chikaodinaka; Fuente, Jayson A. Dela; O. Obih, Solomon A.; Ani, Mercy Ifunanya (International Journal on Integrated Education, 2023)
The study investigated the effect of classroom environment on student’s academic achievement and retention in Basic Science at the upper education level. The study adopted a quasi-experimental design of pretest-posttest, and posttest non-equivalent control group design. Four research questions and four corresponding null hypothesis guided the study. The population of the study was all the upper basic two students in public secondary schools in Enugu State, Nigeria. Two intact classes of Upper Basic Two (JSS2) students were purposively assigned to experimental and control groups. A sample size of 72 upper basic two students was used for the study. A 25-item Basic Science Test (BSAT) was designed by the researchers and used for data collection. Face and content validation were carried out by experts in Basic Science and Measurement and Evaluation. The instrument was trial tested using Kuder-Richardson reliability formula 20 (K-R 20) to determine the reliability coefficient index of 0.85 for the instrument. Mean and standard deviation was used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the null hypotheses at a 0.05 level of significance. The result of the study shows that students exposed to treatment achieved and retain greater knowledge than their counterparts that were denied treatment. It was recommended that low achievers in Basic Science need to be involved more through increased interaction with teachers in the form of makeup classes, tutorial classes, or special coaching.